039. Regulation of carboplatin sensitivity by miRNA in lung cancer cell lines - Petanidis, Savvas (J Thorac Dis, 2015)
Lung cancer chemoresistance is the most common obstacle in lung cancer therapy. Recent studies have indicated that microRNAs play a significant role in this phenomenon and can function as either tumor suppressor or tumor promoters. In the present study we investigated the role of two distinct miR members, the oncomir miR-205 and the tumor suppressor miR-218 concerning the proliferation, invasion and induction of apoptosis in lung cancer cells after carboplatin treatment. The results showed that miR-205 is overexpressed in A549 and H1975 lung cancer cells concurrent with the down regulation of miR-218. Furthermore, ectopic miR-218 overexpression reduced cell proliferation, invasion and migration of lung cancer cells, whereas miR-205 rescued the suppressive effect of miR-218. Our findings suggest that miR-218 play an important role in lung cancer therapy. Tumor suppressor role in inhibiting cancer cell proliferation, and overcoming chemoresistance of miR-218 could be useful in future cancer therapeutic approaches.